The Government of Indonesia's Accountability Against Forest Degradation Due to Deforestation Based on the Paris Agreement to the United Nations Framework Convention on Climate Change - Cherin Ayudia Sari; Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe and explain the form of Indonesia's responsibility for climate change due to deforestation based on the Paris Agreement. As a form of contribution to climate problems, the Government has adopted the Paris Agreement with the instrument Law Number. 16 of 2016. However, the commitment to contribute to reducing greenhouse gas emissions has encountered problems in its implementation. On this basis, this study discusses the state's responsibility for climate change due to deforestation. The main emphasis will be on the forestry sector. This problem is the biggest obstacle in Indonesia's commitment to meet the greenhouse gas emission reduction target. This research method uses normative or doctrinal, the data collection process is carried out by reviewing literature that is relevant to the problems written by the author. The result of this research is that regulations on how to overcome the climate crisis in Indonesia are seen as not being able to implement changes in substance with the ultimate goal of reducing emissions as desired. The issue of effectiveness, especially the problem of legal requirements, is still a principle constraint, even some administrative arrangements contain decisions that contradict the declared responsibilities. In line with that, it is proposed the importance of strong guidelines, implementation of the law and balance of responsibilities through the environmental strategy that is carried out.